2016
DOI: 10.1002/ca.22785
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis of talar trochlea morphology: Implications for subject‐specific kinematics of the talocrural joint

Abstract: Three-dimensional (3D) behavior of the talocrural joint is primarily determined by the articular surface morphology of the talar trochlea and tibiofibular mortise. However, morphological features of the anterior and posterior regions of the talar trochlea remain unclear. The objectives of this study were to evaluate anterior and posterior radii of the medial and lateral talar trochlea and to estimate subject-specific kinematics of the talocrural joint. Fifty dry tali were scanned using computed tomography to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 15 publications
2
25
1
Order By: Relevance
“…Some recent research studies revealed that the talar dome was a saddle-shaped, skewed, truncated cone with laterally oriented apex and the radius of curvature of the lateral border was smaller than the medial border without the fixed rotation axis [1921], which were different from previous conclusions [10]. Furthermore, the unilateral and bilateral asymmetries between the radii of the medial and lateral talar trochleae were found by dividing the trochleae into anterior and posterior regions, in which the anteromedial radius was smaller than anterolateral or posteromedial radius [22]. These results were similar to one early study that medial trochlea had two parts of different radii, whereas the lateral trochlea had one radius [23].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Some recent research studies revealed that the talar dome was a saddle-shaped, skewed, truncated cone with laterally oriented apex and the radius of curvature of the lateral border was smaller than the medial border without the fixed rotation axis [1921], which were different from previous conclusions [10]. Furthermore, the unilateral and bilateral asymmetries between the radii of the medial and lateral talar trochleae were found by dividing the trochleae into anterior and posterior regions, in which the anteromedial radius was smaller than anterolateral or posteromedial radius [22]. These results were similar to one early study that medial trochlea had two parts of different radii, whereas the lateral trochlea had one radius [23].…”
Section: Introductionmentioning
confidence: 84%
“…Better restoration of the morphology of the talar dome is essential to improve the biomechanical research and ankle implant design [11]. However, the results on the radius of the talar dome were controversial, and the repeatability of their methods was not so good [1922, 24, 26]. The current study found that bilateral asymmetry circles of the medial and lateral crests of the talar dome with four parts of different radii resulted in dorsiflexion and plantarflexion axes constantly changing throughout the talocrural joint motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representation of subject-specific anatomy may be particularly important when modeling the ankle due to the highly variable morphology of the talus. 24,35 Multiple studies have described methods to define subject-specific axes of rotation at the tibiotalar and subtalar joints. 2,9,15,16,28,32,36 These include anatomical landmark methods, which use palpable bony landmarks to estimate the location and orientation of joint axes 9,10 ; functional methods, which require axes be fitted to recorded motion 15,31 ; imaging methods, which directly measure helical axes of rotation 2,14,17,32 ; as well as optimization methods, which fit a pre-defined joint model to a measured motion.…”
Section: Introductionmentioning
confidence: 99%
“…Here, tibiotalar and subtalar joint kinematics measured in vivo by dual-fluoroscopy served as the reference standard. Given that the morphology of the talus is highly variable across individuals, 24,35 we hypothesized that there would be significant differences in axes of rotation between the generic and subject-specific models. We further hypothesized that the subject-specific models would provide a more accurate representation of in vivo motion and would thereby predict joint kinematics in better agreement with the dual-fluoroscopy results than generic models.…”
Section: Introductionmentioning
confidence: 99%